EFFECT OF CoCu MEDICA, HIT RIT AND PLACENTREX ON SERUM BIOCHEMICAL PROFILE OF ANESTRUS COWS - AZAD, C S; SINGH, M P; SINGH, BALRAJ; SINHA, M P; SHARMA, D K (The Indian Journal of Animal Reproduction, 2010)
A total number of 40 crossbred anestrus cows were randomly ~!located to four groups viz Gr I(CoCu Medica), Gr. II (HitRit), Gr. Ill (Placentrex) and Gr. IV (Control). Serum biochemical profilesnamely glucose, total protein, calcium, phosphorus, copper and iron were estimated which increasedsignificantly (P
Keywords: Anestrus cows; Serum biochemical profilfl; CoCu Medica; Hit Rlt